2021
DOI: 10.3390/nu13030927
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Intestinal Microbiome, Intestinal Barrier and Psychobiotics in Depression

Abstract: The intestinal microbiota plays an important role in the pathophysiology of depression. As determined, the microbiota influences the shaping and modulation of the functioning of the gut–brain axis. The intestinal microbiota has a significant impact on processes related to neurotransmitter synthesis, the myelination of neurons in the prefrontal cortex, and is also involved in the development of the amygdala and hippocampus. Intestinal bacteria are also a source of vitamins, the deficiency of which is believed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 199 publications
1
61
0
Order By: Relevance
“…Furthermore, systemic administration of butyric acid (which belongs to SCFAs) has been shown to exert antidepressant and neuromodulatory effects [81,82]. The microbiota not only affects the release of various intestinal peptides (peptide YY, glucagon-like peptide 1) but is also involved in their production (Bifidobacterium dentium are able to produce γ-aminobutyric acid (GABA)) [83,84]. In order to investigate the role of the microbiota on HPA axis function, the researchers conducted a study using isolation-cultured mice (GF) [85].…”
Section: Hpa Axis and Gut Microbiotamentioning
confidence: 99%
“…Furthermore, systemic administration of butyric acid (which belongs to SCFAs) has been shown to exert antidepressant and neuromodulatory effects [81,82]. The microbiota not only affects the release of various intestinal peptides (peptide YY, glucagon-like peptide 1) but is also involved in their production (Bifidobacterium dentium are able to produce γ-aminobutyric acid (GABA)) [83,84]. In order to investigate the role of the microbiota on HPA axis function, the researchers conducted a study using isolation-cultured mice (GF) [85].…”
Section: Hpa Axis and Gut Microbiotamentioning
confidence: 99%
“…Elevated levels of IL-1 may be associated with the development of depression, as confirmed by preclinical studies. Impaired social inhibition and reduced sexual activity were observed in test animals [ 70 ]. BDNF affects the formation of new dopaminergic, serotonergic, noradrenergic, and cholinergic connections.…”
Section: Oxidative Stress In Depression and Admentioning
confidence: 99%
“…Due to BDNF’s ability to cross the blood–brain barrier (BBB), its blood concentration is thought to correlate with its concentration in the cerebral cortex. In a study performed on rats, significantly reduced plasma BDNF concentrations were observed in a group of depressed patients compared to a control sample [ 70 , 71 ]. It is possible that the use of antidepressants is associated with the elevated levels of BDNF in serum in patients suffering from depression.…”
Section: Oxidative Stress In Depression and Admentioning
confidence: 99%
“…However, in some cases, the reciprocal relationship becomes skewed, with changes in diet and long-term exposure to antibiotics and other drugs [63]. The contribution of the host's gut-balanced diet to microbial dysfunction and its vital role in coordinating host-microbiome interactions have been demonstrated [64].…”
Section: Dietary Intervention: Improving Intestinal Microbiota Imbalance To Prevent Mental Illnessmentioning
confidence: 99%